2019
DOI: 10.1080/16549716.2018.1553283
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between local weather and leptospirosis incidence in Kandy district, Sri Lanka from 2006 to 2015

Abstract: Background: Leptospirosis is an important public health problem in Sri Lanka. Most people become infected by contact with leptospires in soil and in surface water. Survival of leptospires in the environment depends upon the moisture in soil, humidity, temperature and surface water. Leptospires are spread by flood water and waterways. Therefore, the weather of an area influences the leptospirosis incidence of that area. Objectives: To find out the correlations between the leptospirosis incidence in the district… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 26 publications
7
56
2
1
Order By: Relevance
“…10 Similar results have been found out from studies from Srilanka by Ehelopola et al which showed leptospirosis incidence follows the same pattern of temporal changes of average weekly humidity after a lag period. 12 The current study also found a positive correlation between rainfall and number of leptospirosis cases (Figures 6 and 7A). This relationship have also been found out from the study conducted by Matsushita et al in Philippines who found out that the risk of post-rainfall, leptospirosis peaked at a lag of 2 weeks (using 0 cm/week rainfall as the reference) with RRs of 1.30, 1.53, 2.45, 4.61, and 13.77 for light, moderate, heavy, intense and torrential rainfall (at 2, 5, 16, 32 and 63 cm/week), respectively.…”
Section: Resultssupporting
confidence: 75%
“…10 Similar results have been found out from studies from Srilanka by Ehelopola et al which showed leptospirosis incidence follows the same pattern of temporal changes of average weekly humidity after a lag period. 12 The current study also found a positive correlation between rainfall and number of leptospirosis cases (Figures 6 and 7A). This relationship have also been found out from the study conducted by Matsushita et al in Philippines who found out that the risk of post-rainfall, leptospirosis peaked at a lag of 2 weeks (using 0 cm/week rainfall as the reference) with RRs of 1.30, 1.53, 2.45, 4.61, and 13.77 for light, moderate, heavy, intense and torrential rainfall (at 2, 5, 16, 32 and 63 cm/week), respectively.…”
Section: Resultssupporting
confidence: 75%
“…A previous study has examined bacterial infection and specific weather factors. Ehelopola et al24 observed a direct association between rainfall and humidity and leptospirosis infections in Sri Lanka. As the authors point out, this association is likely attributable to improved survival of leptospires in moist soil.…”
Section: Discussionmentioning
confidence: 98%
“…The diagnosis of the great majority of the reported cases in Sri Lanka is not laboratory confirmed, thus they can be categorized as clinical suspected cases of leptospirosis. Based on this report system, the annual national leptospirosis incidence is 5.4 per 100,000 population [ 51 53 ]. Clinical suspected leptospirosis cases have been reported in the sampling areas [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%